A pH-Responsive Supramolecular Drug Delivery System Constructed by Cationic Pillar[5]arene for Enhancing Antitumor Activity - Liu, Luzhi; Zhou, Qingqing; He, Qin; Duan, Wengui; Huang, Yan (Frontiers in Chemistry, 2021)
Drug delivery systems have good biocompatibiliy and low side effects for cancer treatment, but overcoming high efficiency of drug-loading and the drug-targeting controlled release still remains challenging. In this work, supramolecular vesicles, with pH-triggering effect, have been successfully constructed for drug delivery, which are fabricated by the complexation between a cationic pillar[5]arene (DAWP5) and a sodium dodecyl sulfonate (SDS) in aqueous solution. Drug-loading and releasing results demonstrated that anticancer drug doxorubicin (DOX) could be loaded efficiently by such cationic vesicles in neutral condition, and the drug release could be controlled in the simulated weak acid environment of tumor cells. Moreover, the vesicles had low cytotoxicity to normal human cell (L02), while the DOX-loaded vesicles could significantly enhance the anticancer effect of free DOX for four tested tumor cells (Hela, HepG2, MGC-803 and T24). Especially for HepG2, after 24 h incubation time, IC50 of DOX-loaded vesicles was only 0.79 µM, about 23% of that of DOX (3.43 µM). These results suggested that such novel vesicles have promising potential to construct nano-drug delivery systems for various biomedical applications.